Economics and religion - Carmel Ullman Chiswick (Institute for the Study of Labor (IZA), 2010)
This paper provides an overview of the relationship between economics and religion. It first considers the effects of economic incentives in the religious marketplace on consumers' demand for religion. It then shows how this demand affects religious institutions and generates a supply of religious goods and services. Other topics include the structure of this religious marketplace and the related marketplace for ideas in a religiously pluralistic society. Empirical evidence is summarized for the effects on selected economic behaviors of religious affiliation and intensity of belief or practice.
Keywords: Z12; 330; Economics; religion; human capital; Religion; Mikroökonomik; Humankapital